Managing startups in a globally competitive environment: the role of venture capital in improving business process efficiency - Limar, Vadim (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The aim of this article is to examine the venture capital financing effect on the business process efficiency of the startups in the conditions of global competition. A panel dataset of 10 startups from 2019 to 2023 across a range of industries is analyzed in this study to explore venture capital funding impact on efficiency through global market exposure, innovation intensity and strategic resource allocation. The results finally demonstrate that startups with management teams that have their previous experience managing venture capital funding source are more efficient in their use of the money. These companies are outperforming their sectors both on revenue per employee and long-term competitiveness by making more effective use of resources on topics such as research and development, marketing and operational scalability.